Seismic Capacity Assessment of Existing RC Building by Using Pushover Analysis - Mohammed Ismaeil (Civil Engineering Journal, 2018)
The infrastructure, existing in Sudan, is mostly not structured or designed to resist seismic forces accordingly. The study investigated the seismic damage of a 5 storey existing reinforced concrete building in Khartoum, Sudan. Three performance levels were considered in the study, which included immediate occupancy, life safety, and collapse prevention. The gravity push was carried out using force control method and lateral push with displacement control, using SAP2000. Pushover analysis produces push curve, consisting of capacity spectrum, demand spectrum, and performance point. It showed the performance level of building components along with maximum base shear carrying capacity. It has been observed that demand curve intersected the capacity curve between the points B and C at the X direction that is life safety level; and between the points B and C at the Y direction that is life safety and collapse prevention level. Therefore, some building elements are needed to be strengthened.